Psoriasis patients utilizing secukinumab, ixekizumab, or brodalumab – comparisons to prior biologic medication adherence levels, reasons for switching, and reported changes in disease symptoms. (3rd September 2019) - Baiano, Renee; Staskon, Francis; Miller, Rick
Abstract: Background: Since the approval of interleukin-17 (IL-17) inhibitors to treat psoriasis progression, an increasing number of patients have switched to these third-generation biologics (i.e. secukinumab, ixekizumab, or brodalumab). Little is known about the impact of the new therapy choices upon patient adherence, reasons for switching, or patient reported impacts. Aims: Describe pharmacy utilization for IL-17 inhibitors, and investigate differences from prior biologic treatments (i.e. adalimumab, ustekinumab, or etanercept) on associated medication adherence levels, or patient reported reasons for switching and current disease symptoms after switching. Methods: Pharmacy records from a national specialty pharmacy were examined retrospectively for patients starting an IL-17 inhibitor from January 2016–December 2017, as well as their biologic treatment in the prior 12-months (i.e. adalimumab, ustekinumab, or etanercept). In addition, patient reported information from the clinical management platform was included for those switching from a prior therapy. A 180 day follow-up period was used after starting the IL-17 inhibitor (till May 31, 2018). The medication adherence outcome was the proportion of days covered (PDC) in the observation period (180 days). Excluded patients were under the age of 18 at the start of the new IL-17 inhibitor, or those residing in a US territory. Results: The study sample of 5, 215 consisted of 2, 218 (42.5%) switching from a prior treatment. The most frequent IL-17 inhibitor dispensed was secukinumab (76.1%), followed by ixekizumab (23.7%), and the more frequent prior treatments were etanercept (37%) and adalimumab (35.8%). Gender and age distributions were similar across the IL-17 inhibitors. Medication adherence significantly increased after switching 6.4% on average PDC, and patients were 1.56-times more likely to be adherent (PDC ≥80%); after adjusting for age, gender, census location, and provider specialty. In these multivariate models, the only covariate significantly associated to higher adherence was if the provider specialty was in rheumatology. The most common reason reported for switching was "ineffective treatment" (64.7%). After switching to an IL-17 inhibitor, 45.7% of patients report symptoms as "better", 26.5% the "same", and only 5.3% state "worse" symptoms. Conclusions: Specialty pharmacies offering the recent IL-17 inhibitors allow for additional treatment options for patients needing alternative therapies.